A Modified Particle Swarm Optimization Based Algorithm for the Energy Management Strategy of a Regional Integrated Energy System - CHEN, Yiru; LOU, Fei; JIANG, Ying; YE, Qichao; WANG, Ning; YING, Guangyao (2020 IEEE 9th International Power Electronics and Motion Control Conference (IPEMC2020-ECCE Asia), 2020)
A regional integrated energy system is a structure with a coordinated supply of photovoltaics, wind turbines, micro-turbines and other energy resources. With the goal of improving the energy utilization efficiency and achieving the effective management and coordinated development of a multi-energy system, how to optimize the control of energy has become a significant problem for regional integrated energy systems. This paper establishes a regional integrated energy system with photovoltaics, wind turbines, micro-turbines, and energy storage systems. A modified Particle Swarm Optimization algorithm is used to evaluate the supply cost, and the environment value is proposed to optimize the control of multi-energy.